The sponsorship potential of Slovenian sport - Jurak, Gregor; Bednarik, Jakob; Kovač, Marjeta (Acta Universitatis Carolinae. Kinanthropologica, 2009)
The purpose of this study was to examine the sponsorship potential of Slovenian sport. The sample of measured subjects was a total of 494 potential sponsors/managers of Slovenian companies. A questionnaire was used to examine which sports disciplines are the most interesting for sponsorship, what goals the companies try to fulfil when sponsoring and how the personal attitudes of managers towards sport influences sponsoring. The results of the study revealed that the companies are interested in sponsoring Slovenian sport; however, the range of sports disciplines that interests sponsors is relatively small. The most interesting sports for sponsors are basketball, football, alpine skiing, ski jumping and handball. Compared to previous findings (Bednarik et al., 1998), an increase of the interest for football and a decrease for alpine skiing has been noticed. From the strategic planning point of view, it is important to realize that companies have different sponsorship goals according to their size and that the decision for sponsoring sport is not a result of the individual interest of the manager or his personal affection for sport. The marketing strategy of the company plays a decisive role; currently, the strategy is more directed to the social recognition of the company, its products and services. The most important goals for the sponsorship Slovenian sport are the appearance of the name and the logo of the company, the inclusion of the company in the social environment and improving public opinion of the company. Companies have different sponsorship goals than several years ago (Bednarik et al., 1998); they are particularly more focused on the responsibility and the role of the company in society. In order to attract more sponsorship money, sports organizations will have to approach sponsorship systematically and better present advertising possibilities to potential sponsors. They will also have to develop new products to satisfy sponsorship goals.
Keywords: sporty; průzkumy a dotazníky; Humans; lidé; Industry; Snow Sports; obchod; Surveys and Questionnaires; marketing; průmysl; etika podnikání; Sports; Slovenia; finanční podpora; fotbal; Basketball; Ethics, Business; Slovinsko; Marketing; sporty na sněhu; Financial Support; Commerce; Soccer; basketbal